1990
DOI: 10.1002/tera.1420420111
|View full text |Cite
|
Sign up to set email alerts
|

External genitalia abnormalities in male rats exposed in utero to finasteride, a 5α‐reductase inhibitor

Abstract: A series of studies was conducted to determine the developmental toxicity of the 5 alpha-reductase inhibitor finasteride (MK-0906) in rats. This compound was administered orally once daily to pregnant rats during various extended treatment periods during gestation. F1 offspring were evaluated on Day 20 of gestation as well as postnatally through mating to produce an F2 generation. MK-0906 treatment induced dosage-related incidences of hypospadias (penischisis) in male offspring with a threshold dosage level ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 17 publications
2
65
0
3
Order By: Relevance
“…However, other anti-androgenic chemicals show more shallow dose-response curves. One example of such a substance is the anti-androgenic drug and 5a-reductase inhibitor finasteride (Clark et al 1990, Bowman et al 2003, Christiansen et al 2009). Interestingly, a new study that examines the effects of short-term exposure to BPA on mRNA levels of 5a-reductase isozymes in prostate of adult castrated rats show that BPA significantly decreased the mRNA levels of both 5a-reductase isozymes (Sánchez et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, other anti-androgenic chemicals show more shallow dose-response curves. One example of such a substance is the anti-androgenic drug and 5a-reductase inhibitor finasteride (Clark et al 1990, Bowman et al 2003, Christiansen et al 2009). Interestingly, a new study that examines the effects of short-term exposure to BPA on mRNA levels of 5a-reductase isozymes in prostate of adult castrated rats show that BPA significantly decreased the mRNA levels of both 5a-reductase isozymes (Sánchez et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the crucial role of androgen is based on pharmacological and genetic data. Androgen antagonists (Silversides et al, 1995;Suzuki et al, 2002) or inhibitors of its synthesis (Imperato-McGinley et al, 1985;Clark et al, 1990) interfere with testicular function and external genitalia development. Mutations in androgen receptor gene (Murakami, 1987;Yeh et al, 2002;Sato et al, 2003) or for androgen synthetic enzymes (Andersson et al, 1991;Wilson, 1992) result in abnormalities in male sexual differentiation and development.…”
Section: The Differentiation Of the Gt: Urethra Penis And Clitoris mentioning
confidence: 99%
“…Suppressive effects of flutamide on sexual maturation and behavior have been reported in rats when administered during the perinatal period Brand and Slob, 1991;Zimmerberg and Farley, 1993;Lund et al, 2000) or to offspring immediately after birth Clemens, 1978, 1980;Clemens et al, 1978;Brand and Slob, 1991;Vega Matuszczyk and Larsson, 1995;Miyata et al, 2002). Other chemicals such as antiandrogen drugs finasteride (Clark et al, 1990(Clark et al, , 1993Wise et al, 1991;Imperato-McGinley et al, 1992) and cyproterone acetate , and the estrogen-like chemical bisphenol A (Sato et al, 2001;Cagen et al, 1999) have been reported to cause various changes in morphology of the external genitalia and sexual maturation of the offspring born to mothers treated with these chemicals during pregnancy.…”
Section: Introductionmentioning
confidence: 99%